The effect of 2% salicylic acid as a support of 10% benzoil peroxide gel for mild to moderate acne vulgaris. - Rahajeng Musy, Rahajeng Musy (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Cleansing is necessary before the application of topical therapy for acne vulgaris. However ordinary soap leads to dryness. Two percent salicylic acid has comedolytic, anti inflammation and moisturizing activity.Objective: The aim of this study was to assess the effectiveness of 2% salicylic acid soap as a support of 10% benzoil peroxide gel for mild to moderate acne vulgaris.Material and method: The design of this study was randomized, double blind, clinical trial. Fifty twofemales with mild to moderate acne vulgaris with the mean of the age was 18.9 ÃÂ± 3.06 years old were divided into 2 groups. The first group was treated with 2% salicylic acid soap and the second group was treated with soap base, in addition to 10% benzoil peroxide gel for both groups. The clinical assessment was conducted by counting the acne lesion at 2, 4, 8, and 12 week. While the level of moisture and sebum of the skin was measured by corneometer and sebumeter of Courage Ã¢â¬â Khazaka at 4, 8, and 12 week. The difference between 2 groups was analyzed statistically by t-test, chi-square test and Mann-Whitney U test. The difference was considered to be significant if p < 0.05.Result: There was significant reduction of the open comedone in salicylic acid soap groupÂ